Применение алгоритма расчета в частотной области для ультразвуковой томографии; Дефектоскопия; № 4 - Долматов Д. О. Дмитрий Олегович; Демянюк Д. Г. Дмитрий Георгиевич; Седнев Д. А. Дмитрий Андреевич; Пинчук Р. В. Роман Валерьевич (Акустические методы, 2018)
Заглавие с экрана